A potential biotechnological process for the sustainable production of vitamin K1. (2nd January 2019) - Tarento, Thomas D. C.; McClure, Dale D.; Talbot, Andrea M.; Regtop, Hubert L.; Biffin, John R.; Valtchev, Peter; Dehghani, Fariba; Kavanagh, John M.
Abstract: The primary objective of this review is to propose an approach for the biosynthesis of phylloquinone (vitamin K1 ) based upon its known sources, its role in photosynthesis and its biosynthetic pathway. The chemistry, health benefits, market, and industrial production of vitamin K are also summarized. Vitamin K compounds (K vitamers) are required for the normal function of at least 15 proteins involved in diverse physiological processes such as coagulation, tissue mineralization, inflammation, and neuroprotection. Vitamin K is essential for the prevention of Vitamin K Deficiency Bleeding (VKDB), especially in neonates. Increased vitamin K intake may also reduce the severity and/or risk of bone fracture, arterial calcification, inflammatory diseases, and cognitive decline. Consumers are increasingly favoring natural food and therapeutic products. However, the bulk of vitamin K products employed for both human and animal use are chemically synthesized. Biosynthesis of the menaquinones (vitamin K2 ) has been extensively researched. However, published research on the biotechnological production of phylloquinone is restricted to a handful of available articles and patents. We have found that microalgae are more suitable than plant cell cultures for the biosynthesis of phylloquinone. Many algae are richer in vitamin K1 than terrestrial plants, and algal cells are easier to manipulate. Vitamin K1 can be efficiently recovered from the biomass using supercritical carbon dioxide extraction.